2019
DOI: 10.5513/jcea01/20.4.2277
|View full text |Cite
|
Sign up to set email alerts
|

The investigation of suitability of raw milk consumption from vending machines in Croatia

Abstract: The consumption of raw milk from vending machine in Croatia has increased in recent years. However, its health safety is insufficiently investigated and controlled. The objective of this study was to investigate the suitability of raw milk consumption, from 28 vending machines from 3 counties in Croatia during one-year research period, based on the physicochemical and hygiene quality. Also, the simulation of psychrothrophic bacteria growth has been conducted in order to determine its optimal storage time becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…They cited research that had proven the presence of listeria monocytogenes and other pathogen microbes in milk vending machines (c.f. Mikulec et al, 2019) as evidence of this.…”
Section: Introductionmentioning
confidence: 81%
“…They cited research that had proven the presence of listeria monocytogenes and other pathogen microbes in milk vending machines (c.f. Mikulec et al, 2019) as evidence of this.…”
Section: Introductionmentioning
confidence: 81%
“…Some of the identified articles reported vending samples with relatively low levels of milk contamination (Bianchi et al ., 2013; Dalzini et al ., 2016) corresponding to well‐established national and international standards for microbiological quality (Angelidis et al ., 2016; Vietoris et al ., 2016; Torkar et al ., 2017; Zdolec et al ., 2019). However, the level of microbiological quality varies according to the methodological approach used to test the milk samples (Giacometti et al ., 2012; Mikulec et al ., 2019; Zdolec et al ., 2019). Bianchi et al .…”
Section: Review Findingsmentioning
confidence: 99%
“…Moreover, the risk of foodborne diseases does not exist when milk has been stored properly (4°C) or consumed boiled (Giacometti et al ., 2015). Therefore, interactive games are recommended to raise awareness of young consumers on the potential risks of drinking raw milk (Crovato et al ., 2016) and the need for a thermal treatment of milk prior to consumption (Giacometti et al ., 2012; Tremonte et al ., 2014; Mikulec et al ., 2019; Traversa et al ., 2019). In countries like Italy, where vending channels are frequently used for selling raw milk, national authorities established strict rules to satisfy the hygiene and informational needs of vending customers.…”
Section: Review Findingsmentioning
confidence: 99%
“…Previous studies show that the quality and safety of pasteurized milk is highly compromised at the retail points [3]. A study on the suitability of milk for consumption found pathogenic microorganisms in milk that had been stored for retail [4], and another study evaluating the microbial quality of pasteurized milk found high total viable counts and coliform bacteria in pasteurized milk [5].…”
Section: Introductionmentioning
confidence: 99%